2016
DOI: 10.1177/0022002715569772
|View full text |Cite
|
Sign up to set email alerts
|

The Distinctive Effects of Empathy and Hope in Intractable Conflicts

Abstract: The goal of the current research was to examine how discrete positive intergroup emotional phenomena affect conflict-related attitudes in different contexts of intractable conflict. We hypothesized that empathy, but not hope would be negatively associated with aggressive attitudes during escalation, while hope, but not empathy would be associated with conciliatory attitudes during de-escalation. In study 1, we examined our hypotheses within a correlational design in an emotioninducing context, while in study 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 87 publications
4
81
2
2
Order By: Relevance
“…In terms of promoting conflict resolution, recent research has begun to address intergroup emotions as possible tools for reconciliation as well. For example, in the context of intergroup relations, empathy has been found to raise the motivation to alleviate the suffering of others (Batson, Chang, Orr, & Rowland, 2002), it frequently results in helping behavior and altruistic motivations (Cikara, Bruneau, Van Bavel, & Saxe, 2014;Waytz, Zaki, & Mitchell, 2012), and it is negatively correlated with any kind of aggression even in the context of intractable conflict (Rosler, Cohen-Chen, & Halperin, 2017;Shechtman & Basheer, 2005). Similarly, group-based guilt has been found to be a crucial step on the path toward reparation and reconciliation (Brown, Gonzalez, Zagefka, Manzi, & Cehajic, 2008) and to raise motivation to repair the damage caused by the behavior of one's in-group (Čehajić, Effron, Halperin, Liberman, & Ross, 2011;Doosje, Branscombe, Spears, & Manstead, 1998).…”
Section: Emotions In Intergroup Conflictmentioning
confidence: 99%
“…In terms of promoting conflict resolution, recent research has begun to address intergroup emotions as possible tools for reconciliation as well. For example, in the context of intergroup relations, empathy has been found to raise the motivation to alleviate the suffering of others (Batson, Chang, Orr, & Rowland, 2002), it frequently results in helping behavior and altruistic motivations (Cikara, Bruneau, Van Bavel, & Saxe, 2014;Waytz, Zaki, & Mitchell, 2012), and it is negatively correlated with any kind of aggression even in the context of intractable conflict (Rosler, Cohen-Chen, & Halperin, 2017;Shechtman & Basheer, 2005). Similarly, group-based guilt has been found to be a crucial step on the path toward reparation and reconciliation (Brown, Gonzalez, Zagefka, Manzi, & Cehajic, 2008) and to raise motivation to repair the damage caused by the behavior of one's in-group (Čehajić, Effron, Halperin, Liberman, & Ross, 2011;Doosje, Branscombe, Spears, & Manstead, 1998).…”
Section: Emotions In Intergroup Conflictmentioning
confidence: 99%
“…More recent examinations have also shown that empathy can causally contribute to both support for constructive and humanitarian policies (Pliskin, Bar‐Tal, Sheppes, & Halperin, ) and actual helping behavior (Mashuri, Hasanah & Rahmawati, ) in intergroup contexts. Generally, however, it seems that empathy specifically results in increased willingness to help the group, through actions such as humanitarian aid, and is not a general motivator for policy change or conciliatory measures (Rosler, Halperin, & Cohen‐Chen, N.d.).…”
Section: Emotions In Intractable Conflictsmentioning
confidence: 99%
“…A growing body of research has begun to explore the role of hope in promoting intergroup reconciliation. Hope involves an expectation of a positive anticipated outcome (Rosler, Cohen-Chen, & Halperin, 2015). In conflict settings, hope can increase concession-making (Cohen-Chen, Halperin, Crisp, & Gross, 2013), endorsement of problem-solving strategies to resolve conflict (Baron, Fortin, Frei, Hauver, & Shack, 1990;Čehajić, Brown, & Castano, 2008;Halperin, Bar-Tal, Nets-Zehngut, & Drori, 2008), support for humanitarian aid to out-groups (Halperin & Gross, 2011), and willingness to forgive the perpetrator group (Moeschberger, Dixon, Niens, & Cairns, 2005).…”
Section: The Role Of Emotions: Anger and Hopementioning
confidence: 99%